KERJASAMA INDONESIA – CHINA: TRANSFER TEKHNOLOGI DIBIDANG INDUSTRI PERTAHANAN (STUDY KASUS PEMBUATAN RUDAL C-705) - Wulandari, Arum Fitria (Transformasi, 2015)
This study aims to find out the bilateral cooperation between Indonesia and China in the fieldof technology transfer of Missile Defense Industries C-705 where each country has a nationalinterest that must be met from the economic, political, social, military security and it is thusthis cooperation forged by the two countries to solve the national problems of the twocountries. It describes the process of the cooperation between Indonesia and China regardingthe transfer of missile technology C-705. This cooperation is intended with the aim to meetthe needs and interests of both countries as well as the fulfillment of the purpose of thetransfer of this technology is for the independence of Indonesia's defense industry so thatIndonesia can produce The Main tool of defense system independently.With this cooperation,Indonesia can modernize The Main tool of defense Indonesia. Indonesian seeks for a goodfriend to not always depend on the west countries in the supply of The Main tool of defensesystem. In the economy is expected to eventually Indonesia The Main tool of defense systemmarket, in the field of security with the manufacture of C-705 missiles Indonesia's securitywould be stronger, especially in the maritime field. With the cooperation, China wants todominate politically Asian Countries through Indonesia because Indonesia is the largestcountry in Asia. On the other sides Indonesia are also expected to supply energy to Chinawhile in the security field is stronger to China region succumbing to the influence of the west.Indonesia and China entered into a collaboration because each country wants to achieve itsnational interests which such cooperation can be mutually beneficial.Key Words : Cooperation , Defence , National Interests , C - 705 missile